EFFECTIVENESS OF THE E-MUTATION APPLICATION IN PROPOSING PERIODIC SALARY INCREASES FOR CIVIL SERVANTS TOWARDS GOOD GOVERNANCE IN BKD SOUTH KALIMANTAN - Muhammad Wildiannor Khair; Budi Kristanto (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2025)
This study evaluates the implementation of the E-Mutasi application in the process of proposing periodic salary increases for Civil Servants (PNS) at the Regional Civil Service Agency (BKD) of South Kalimantan. The application is designed to enhance the efficiency of civil service administration through process digitalization, reducing the use of physical documents, and accelerating decision-making. The study employs a descriptive qualitative approach using observation and interviews. The findings indicate that the E-Mutasi application supports the principles of good governance, such as transparency, efficiency, and accountability, despite encountering technical challenges, including limited file upload capacity and insufficient training for new users. Recommended solutions include increasing server capacity, integrating the application with the employee information system, and providing continuous training for personnel administrators. With these optimizations, the E-Mutasi application is expected to improve the quality of public services and support bureaucratic reform toward better governance.